2018
DOI: 10.1186/s12920-018-0326-1
|View full text |Cite
|
Sign up to set email alerts
|

Primary microcephaly case from the Karachay-Cherkess Republic poses an additional support for microcephaly and Seckel syndrome spectrum disorders

Abstract: BackgroundPrimary microcephaly represents an example of clinically and genetically heterogeneous condition. Here we describe a case of primary microcephaly from the Karachay-Cherkess Republic, which was initially diagnosed with Seckel syndrome.Case presentationClinical exome sequencing of the proband revealed a novel homozygous single nucleotide deletion in ASPM gene, c.1386delC, resulting in preterm termination codon. Population screening reveals allele frequency to be less than 0.005. Mutations in this gene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…In addition to RHDs that are frequent for all populations of the Russian Federation and Europe, regionally specific diseases have been identified. Our study identified diseases endemic to specific regions of the Russian Federation-several types of hypotrichosis (Kazantseva et al, 2006;Zernov et al, 2016), osteopetrosis (Bliznetz et al, 2009), and a number of RDs identified in the Russian Federation and worldwide in single cases-primary microcephaly (Marakhonov et al, 2018), gnathodiaphyseal dysplasia (Andreeva et al, 2016), metatropic dysplasia (Timkovskaya et al, 2016), etc.…”
Section: Resultsmentioning
confidence: 98%
“…In addition to RHDs that are frequent for all populations of the Russian Federation and Europe, regionally specific diseases have been identified. Our study identified diseases endemic to specific regions of the Russian Federation-several types of hypotrichosis (Kazantseva et al, 2006;Zernov et al, 2016), osteopetrosis (Bliznetz et al, 2009), and a number of RDs identified in the Russian Federation and worldwide in single cases-primary microcephaly (Marakhonov et al, 2018), gnathodiaphyseal dysplasia (Andreeva et al, 2016), metatropic dysplasia (Timkovskaya et al, 2016), etc.…”
Section: Resultsmentioning
confidence: 98%
“…Numerous studies have shown that the frequencies of Mendelian diseases and different pathogenic variants can vary significantly among different regions of Russia [35][36][37][38][39][40][41][42]. Although Russians are the major ethnic group in Russia (111 million out of the total population of 146 million), there is a significant number of indigenous ethnic populations living for hundreds of years in their historical locations (over 200 different ethnicities and ethnic groups, according to the 2010 Census) unevenly dispersed across the vast territory of Russia [34].…”
Section: Discussionmentioning
confidence: 99%
“…In the Circassian family with primary microcephaly and mental retardation type 5, NGS sequencing revealed a novel homozygous single nucleotide deletion NM_018136.4 (ASPM):c.1386delC leading to a preterm stop codon formation. A population analysis (202 chromosomes from healthy Circassians) shows that the population frequency of the c.1386delC variant is less than 0.005 [22].…”
Section: Genetic Heterogeneity (Allelic Locus) Of Monogenic Hereditamentioning
confidence: 99%
“…Polyakov). Variety of methods were used for DNA diagnosis-Sanger sequencing, MLPA, RFLP, AFLP, whole exome sequencing-Depending on the studied nosology according to the protocols published elsewhere by the authors of current manuscript [19][20][21][22][23].…”
Section: Molecular Genetic Analysismentioning
confidence: 99%